Perancangan Instalasi Air Limbah (IPAL) Domestik Di Laundri Dan Kantin Rumah Sakit X Pekanbaru - Khatami Achmad; Aryo Sasmita; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Hospital X in pekanbaru is the hospital of the mother and child special private in pekanbaru. In the process of wastewater treatment, the laundry facilities and cafeteria of the hospital do not enter the treatment process at the wwtp so that still needs further processing in order not to pollute the surrounding environment. It is based on and Permen LH No. 5 2014 the attachment 44 about the Quality of the Raw Waste Water For Business and/or Activities of Health care Facilities. Given the problem, the development of waste treatment facilities that are appropriate and cheap in terms of technology, price and ease of operation is very important. In this paper described the design of the waste water treatment plant (WWTP) with biological treatment to appropriate hospital namely with the process of wastewater treatment biofilter anaerobic aerobic with a capacity of 6,615 m3/day. The results showed that based on the calculation and design that has been made, the WWTP that will be used as a waste water treatment system of Hospital X can be overcome or cope with the problem of environmental pollution. It is seen from the level of the decreased efficiency of processing is quite high, namely BOD 5.35 mg/L (99,4%), COD 33,9 mg/L (98,4%), TSS 1.6 mg/L (99.8% Of), Total Coliform 103,125 MPN/100 mL (99%), MBAS 5,625 mg/L (of 97.7%), and the content of Oil and Fat of 13.5 mg/L (to 97.5%). Budget the cost needed to build a WWTP in the amount of Rp,60.000.000.00,-. Keywords: Aerobic-Anaerobic Biofilter, Hospital Waste Water, Raw Quality